Modelling the fate of nitrite in an urbanized river using experimentally obtained nitrifier growth parameters. (15th April 2015) - Raimonet, Mélanie; Vilmin, Lauriane; Flipo, Nicolas; Rocher, Vincent; Laverman, Anniet M.
Abstract: Maintaining low nitrite concentrations in aquatic systems is a major issue for stakeholders due to nitrite's high toxicity for living species. This study reports on a cost-effective and realistic approach to study nitrite dynamics and improve its modelling in human-impacted river systems. The implementation of different nitrifying biomasses to model riverine communities and waste water treatment plant (WWTP)-related communities enabled us to assess the impact of a major WWTP effluent on in-river nitrification dynamics. The optimal kinetic parameters and biomasses of the different nitrifying communities were determined and validated by coupling laboratory experiments and modelling. This approach was carried out in the Seine River, as an example of a large human-impacted river with high nitrite concentrations. The simulation of nitrite fate was performed at a high spatial and temporal resolution (Δ t  = 10 min, d x ¯  = 500 m) including water and sediment layers along a 220 km stretch of the Seine River for a 6-year period (2007–2012). The model outputs were in good agreement with the peak of nitrite downstream the WWTP as well as its slow decrease towards the estuary. Nitrite persistence between the WWTP and the estuary was mostly explained by similar production and consumption rates of nitrite in both water and sediment layers. The sediment layer constituted a significant source of nitrite, especially during high river discharges (0.1–0.4 mgN h −1  m −2 ). This points out how essential it is to represent the benthic layer in river water quality models, since it can constitute a source of nitrite to the water-column. As a consequence of anthropogenic emissions and in-river processes, nitrite fluxes to the estuary were significant and varied from 4.1 to 5.5 TN d −1 in low and high water discharge conditions, respectively, over the 2007–2012 period. This study provides a methodology that can be applied to any anthropized river to realistically parametrize autochthonous and WWTP-related nitrifier communities and simulate nitrite dynamics. Based on simulation analysis, it is shown that high spatio-temporal resolution hydro-ecological models are efficient to 1) estimate water quality criteria and 2) forecast the effect of future management strategies. Process-based simulations constitute essential tools to complete our understanding of nutrient cycling, and to decrease monitoring costs in the context of water quality and eutrophication management in river ecosystems. Graphical abstract: Highlights: A cost-efficient approach allows studying nitrification and WWTP impact on nitrite dynamics. External load & in-stream biogeochemical processes alter nitrite dynamics in anthropized river. Benthic sediments have a significant impact on river water quality. Hydro-ecological models allow assessing water quality criteria at small spatio-temporal scales.